TRADOS APPLICATION DEVELOPMENT IN BIRA VILLAGE BASED ON ANROID - Ghina Mardhiyah, Fairuz; Imran, Al; T Mangesa , Riana (Jurusan Pendidikan Teknik Elektro, 2025)
The development of the Trados application for tourists visiting the Bira Beach area in Bulukumba Regency aims to streamline the booking process for accommodations, food, and transportation services through an Android-based mobile platform. This research follows a Research and Development (R&D) methodology and utilizes the Waterfall model for systematic application development, encompassing stages such as requirement analysis, design, coding, testing, and maintenance. The study involved interviews and questionnaires with tourists and local service providers to gather data on user needs and preferences. The application was developed using Java programming in Visual Studio Code and tested for functionality, usability, performance efficiency, and portability. Results showed the app meets ISO 25010 standards, with excellent usability (90%), satisfactory performance efficiency, and portability across different Android devices. Despite its success, the study acknowledges limitations such as the small sample size and the lack of real-time booking updates or third-party service integrations. Future research should focus on enhancing the app's functionality and expanding its user base to improve service delivery and user experience in tourism-related applications.